2010
DOI: 10.1016/j.hitech.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Complementarities in the implementation of advanced manufacturing technologies

Abstract: The purpose of this analysis is to use complementarity analysis to explain why some implementations of advanced manufacturing technology (AMT) provide a high return on investment while others do not. By analysing the engineering environment, as well as the technology used in the manufacturing process, we hope to provide further insight into the necessary environmental conditions for high returns on investments in AMT. This paper aims to advance current understanding of the impact of organizational fit through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…According to Goyal and Grover [12], manufacturing evolves continuously and the adoption of AMT is usually due to the intention to improve some of the competitive factors, such as delivery, cost, quality, or flexibility, in line with Kotha and Swamidass [11]. Percival [13] finds that, besides the widely stated benefits of improving own performance, AMT can also represent an entry barrier for competition. Her main theoretical findings are that AMT reduces the need for unskilled workers, but it augments the demand for skilled workers, which eventually may not reduce labour costs.…”
Section: Effects Of Advanced Manufacturing Technologies On Manufacturmentioning
confidence: 99%
“…According to Goyal and Grover [12], manufacturing evolves continuously and the adoption of AMT is usually due to the intention to improve some of the competitive factors, such as delivery, cost, quality, or flexibility, in line with Kotha and Swamidass [11]. Percival [13] finds that, besides the widely stated benefits of improving own performance, AMT can also represent an entry barrier for competition. Her main theoretical findings are that AMT reduces the need for unskilled workers, but it augments the demand for skilled workers, which eventually may not reduce labour costs.…”
Section: Effects Of Advanced Manufacturing Technologies On Manufacturmentioning
confidence: 99%
“…Westhead, Wright, and Ucbasaran (2004) studied the exporting propensity and firm operation using a weighted group of performance proxies such as sales revenue growth, return of equity, and both gross and net profits by multivariate regression for cross-sectional data. Percival (2004), in her dissertation work dealing with the realization of advanced manufacturing technologies, implements penalties in one solution of factor analysis. The other type of penalties can be defined considering, e.g., the temporal weights for individual observations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that up to 45 different types of AMTs are listed in the literature. The set of technologies that can be considered to be AMTs in this study is based on a literature review by several authors [9,[33][34][35][36][37][38][39]. The AMTs which are very frequently mentioned are: computer-aided design (CAD), robots, computer-aided manufacturing (CAM), computer numerical control (CNC), flexible manufacturing systems (FMS) and manufacturing resource planning (MRPII).…”
Section: Advanced Manufacturing Technologiesmentioning
confidence: 99%